Best options for the exposure of traditional and innovative moss bags: A systematic evaluation in three European countries. (July 2016) - Capozzi, F.; Giordano, S.; Aboal, J.R.; Adamo, P.; Bargagli, R.; Boquete, T.; Di Palma, A.; Real, C.; Reski, R.; Spagnuolo, V.; Steinbauer, K.; Tretiach, M.; et al.
Abstract: To develop an internationally standardized protocol for the moss bag technique application, the research team participating in the FP7 European project "MOSSclone" focused on the optimization of the moss bags exposure in terms of bag characteristics (shape of the bags, mesh size, weight/surface ratio), duration and height of exposure by comparing traditional moss bags to a new concept bag, "Mossphere". In particular, the effects of each variable on the metal uptake from the air were evaluated by a systematic experimental design carried out in urban, industrial, agricultural and background areas of three European countries with oceanic, Mediterranean and continental climate. The results evidenced that the shape, the mesh size of the bags and the exposure height (in the tested ranges), did not significantly influence the uptake capacity of the transplanted moss. The aspects more affecting the element uptake were represented by the density of the moss inside the bags and the relative ratio between its weight and the surface area of the bag. We found that, the lower the density, the higher the uptake recorded. Moreover, three weeks of exposure were not enough to have a consistent uptake signal in all the environments tested, thus we suggest an exposure period not shorter than 6 weeks, which is appropriate in most situations. The above results were confirmed in all the countries and scenarios tested. The adoption of a shared exposure protocol by the research community is strongly recommended since it is a key aspect to make biomonitoring surveys directly comparable, also in view of its recognition as a monitoring method by the EU legislation. Highlights: Variables affecting moss bag uptake were tested by systematic experimental design. Variables investigated were: shape, mesh size, density, height and exposure time. A new concept bag "Mossphere" was developed. Uptake effectiveness was evaluated in four scenarios of three EU countries. The variables most affecting uptake are moss density and exposure time. Abstract : Variables significantly affecting moss bag uptake are exposure time and moss weight/bag surface ratio.